2015
DOI: 10.3109/09593985.2014.1003343
|View full text |Cite
|
Sign up to set email alerts
|

Treating gynecological pain: the experiences of bachelor students in physiotherapy performing somatocognitive therapy

Abstract: Contrary to expectations, the students experienced the application of this combined approach (SCT) as an interesting and rewarding way of working with patients, and that they had achieved skills and a sufficient set of tools to cope with the challenges that patients with longstanding gynecological pain represent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
13
0
2
Order By: Relevance
“…In a care situation, a calm, frank discussion between a vulvodynia patient and a healthcare professional about this intimate problem has been found to foster a sense of trust in women patients. In turn, this sense of trust facilitates a more detailed description of her vulvodynia symptoms and intimate problems (1,55). It is also found that women with newly diagnosed vulvodynia are open to counselling to address the psychosexual aspects of their vulvar pain, and they report that it has helped them to cope with intimacy problems (56).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a care situation, a calm, frank discussion between a vulvodynia patient and a healthcare professional about this intimate problem has been found to foster a sense of trust in women patients. In turn, this sense of trust facilitates a more detailed description of her vulvodynia symptoms and intimate problems (1,55). It is also found that women with newly diagnosed vulvodynia are open to counselling to address the psychosexual aspects of their vulvar pain, and they report that it has helped them to cope with intimacy problems (56).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, good, experienced‐based skills in discussing intimate issues naturally were associated with the abovementioned dimensions of awareness. Possibly due to the naturalness of these conversations, healthcare professionals' awareness increased through patient‐oriented communication . In a care situation, a calm, frank discussion between a vulvodynia patient and a healthcare professional about this intimate problem has been found to foster a sense of trust in women patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This involved experiencing the different sensations elicited by warm and cold cloths and showers, as well as gently exploring the vulva with their fingers, self-massaging, and alternating between tensing and relaxing the muscles of the pelvic floor. Patients were encouraged to use tampons of gradually increasing size (Fougner and Haugstad, 2015). In SCT, an important goal for the patient is to develop body awareness, gain new bodily experiences, and develop coping strategies and a sense of mastery of one's own life (see a further description in (Haugstad et al, 2011).…”
Section: Somatocognitive Therapy (Sct)mentioning
confidence: 99%
“…Marit Fougner, this paper's second author, is a physiotherapist with 28 years of experience as a preclinical teacher for an educational programme in physiotherapy. Personal experiences with TRE and a study of body-mindfulness techniques in chronic pain management (Fougner & Killi Haugstad 2015) became an incentive to explore acting students' experiences for possible stress regulatory strategies promoting self-knowledge and self-care among students in different programmes.…”
Section: Introductionmentioning
confidence: 99%